Toward up-scaling the four-terminal all-perovskite tandem solar modules on flexible substrates. (August 2022) - Babu, Vivek; Mejia Escobar, Mario Alejandro; Fuentes Pineda, Rosinda; Ścigaj, Mateusz; Spinelli, Pierpaolo; Wojciechowski, Konrad
Abstract: Multijunction all-perovskite solar cells hold a great promise for reaching record high power conversion efficiency values. Additionally, the employment of flexible substrates provides attractive new functionalities, opening many new commercial exploitation routes. The present state-of-the-art of the flexible perovskite tandem devices is limited to very small areas and non-scalable fabrication methods. Here, the development of large-area blade-coating of wide- and narrow-bandgap perovskite photoactive layers on flexible substrates is reported. Optimized sub-junctions are assembled into the 4-terminal tandem solar modules, delivering 15.3% efficiency for the 50 cm 2 active area. Applied surface modification strategies and interfacial engineering for both perovskite sub-modules, together with the robust flexible encapsulation, delivers promising reliability results, achieved in different indoor and outdoor aging tests. Graphical abstract: Image 1 Highlights: Scalable deposition of wide- and narrow-bandgap perovskite photoactive layers. Fabrication of large-area flexible perovskite solar modules based on wide- and narrow-bandgap perovskite films. Developed flexible, roll-to-roll encapsulation protocol, enabling good reliability in indoor and outdoor aging tests. Flexible four-terminal all-perovskite tandem photovoltaic module reaching 15.3% of power conversion efficiency.